Digital health technologies for metabolic disorders in older adults: a scoping review protocol - Michael Brändle; Elgar Fleisch; Tobias Kowatsch; Panitda Huynh; Mia Jovanova (BMJ Open)
Introduction Metabolic disorders (type 2 diabetes, insulin resistance, hyperglycaemia, obesity, hyperlipidaemia, hypertension, non-alcoholic fatty liver disease and metabolic syndrome) are leading causes of mortality and disability worldwide. These disorders disproportionately affect older adults relative to those younger. Digital health technologies (DHTs), such as patient monitoring, digital diagnostics and digital therapeutics, emerge as promising tools for health promotion in day-to-day life. However, their role in targeting metabolic disorders, particularly among a key demographic of older adults, is not yet fully understood. Thus, this study aims to scope the use of DHTs in managing metabolic health disorders among older adults. To our knowledge, this is the first review to categorise DHTs for older adults with metabolic disorders, contributing to the growing literature in the intersection of metabolic disorders and DHTs.Methods and analysis We will conduct a scoping review following the recommended framework by Arksey and O’Malley. Our search will focus on three primary concepts: metabolic disorders, DHTs and older adults. We plan to search five online databases (Cochrane, ScienceDirect, PubMed, Scopus and Web of Science) to identify original research articles published between January 2014 and January 2024. Two independent reviewers will screen articles based on predefined eligibility criteria, with a third reviewer resolving conflicts. Data will be extracted using a standardised form, and results will be synthesised qualitatively and quantitatively. The database searches, data collection and analysis are planned and have not been conducted.Ethics and dissemination No ethics approval is required for this protocol and scoping review. Data will be used only from published studies with appropriate ethics approval. Results will be disseminated in a peer-reviewed publication.